Correlation Between Continuous Assessment And End Of Posting Performance: The Importance Of Assessment Methods And Rubrics - Norwati, Daud; Harmy, Mohamed Yusoff; Nurulhuda, Mat Hassan (2017)
Competence in medicine is defined as “the habitual and judicious use of communication, knowledge, technical skills, clinical reasoning, emotions, values, and reflection in daily practice for the benefit of the individuals and communities being served.” 1 Assessment method is important in determining clinical performance. Assessment relies strongly on how good the marking scheme is and it should reflect the true performance of students. One of the grading instrument used in assessment in rubrics. Rubrics is shown to guide students to plan for their assessment and reduce anxiety as they can focus on what the assessment wants. 2 Good rubrics is shown to increase rater reliability as they lead to a similar interpretation of student performance. 3 In addition to that, validity of rubrics depends of clarity and appropriateness of language. This study aimed to determine the correlation between continuous assessment and end of posting performance of family medicine rotation before and after an improved assesment method and rubrics for continous assessment